2022
DOI: 10.3389/fgene.2022.856493
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Disease Associated CLEC16A Variants Convey Risk of Parkinson’s Disease in Han Chinese

Abstract: CLEC16A is a membrane-associated endosomal protein implicated in regulating autophagy and antigen presentation. Its genetic variants are broadly associated with multiple autoimmune diseases. Parkinson’s disease (PD), which undergoes autophagy disruption and neuroinflammation, has been clinically observed, for an extensive amount of time, to be associated with autoimmune diseases. In this study, we aimed to understand whether the autoimmune disease associated CLEC16A variants pleiotropically modulate PD risk. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Several studies have shown consistent association of heterozygous CLEC16A SNPs with auto-immune disorders, particularly multiple sclerosis (International Multiple Sclerosis Genetics Consortium 2009;International Multiple Sclerosis Genetics Consortium et al 2007;Nischwitz et al 2011), type-1 diabetes (Hakonarson et al 2007;Wellcome Trust Case Control Consortium 2007), and Crohn's disease (Marquez et al 2009), and that CLEC16A plays a role in the neurodegeneration of Parkinson disease (Fan et al 2022; 7a) and corrected for total protein (Supplementary Fig. 7b).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies have shown consistent association of heterozygous CLEC16A SNPs with auto-immune disorders, particularly multiple sclerosis (International Multiple Sclerosis Genetics Consortium 2009;International Multiple Sclerosis Genetics Consortium et al 2007;Nischwitz et al 2011), type-1 diabetes (Hakonarson et al 2007;Wellcome Trust Case Control Consortium 2007), and Crohn's disease (Marquez et al 2009), and that CLEC16A plays a role in the neurodegeneration of Parkinson disease (Fan et al 2022; 7a) and corrected for total protein (Supplementary Fig. 7b).…”
Section: Discussionmentioning
confidence: 82%
“…Unlike other CLEC proteins, CLEC16A lacks an active/full length carbohydrate recognition domain and functions as an E3-ubiquitin ligase involved in the regulation of autophagy and mitophagy (Kim et al 2010Pearson et al 2018;Redmann et al 2016;Soleimanpour et al 2014). Despite the absence of a functional carbohydrate recognition domain, several GWAS studies have shown a link between CLEC16A and the human immune system by associating the CLEC16A locus with susceptibility to auto-immune diseases, including type-1 diabetes (Hakonarson et al 2007;Wellcome Trust Case Control Consortium 2007), multiple sclerosis (International Multiple Sclerosis Genetics Consortium 2009;International Multiple Sclerosis Genetics Consortium et al 2007;Nischwitz et al 2011), primary biliary cholangitis (Hirschfield et al 2012), Addison disease (Skinningsrud et al 2008), juvenile idiopathic arthritis (Skinningsrud et al 2010), and neurodegenerative disorders like Parkinson disease (Fan et al 2022;Strafella et al 2021). CLEC16A is thought to regulate immune tolerance via the endosome-lysosome trafficking by stimulating autophagy of thymic epithelial cells and lowering of the antigen-presenting function (Schuster et al 2015), by the regulation of HLA class-II antigen expression via late endosome biogenesis in antigen-presenting cells and by participating in retrograde transport of HLA-II containing compartments in myeloid cells (Li et al 2015;Rijvers et al 2020;van Luijn et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variants were annotated for functions as previously described ( Fan et al, 2022 ). In brief, potential causal links to diseases were annotated using HaploReg ( http://pubs.broadinstitute.org/mammals/haploreg/haploreg.php ).…”
Section: Methodsmentioning
confidence: 99%
“…To some extent this is evident in all people, but it is classified as an autoimmune disease when this self-reactivity leads to tissue damage (either systemic or local). There are numerous well-established 'autoimmune' (or immunemediated) diseases, such as multiple sclerosis, type 1 diabetes (T1DM) and rheumatoid arthritis as well as a growing number of diseases that have an important autoimmune aspect to their pathophysiology, such as Parkinson's disease [18], amyotrophic lateral sclerosis (ALS) [19] and Alzheimer's disease [20], with developing treatments now being shaped by the 'autoimmune aspects' of these classical neurodegenerative conditions [21].…”
Section: Classical Autoimmunitymentioning
confidence: 99%